2009
DOI: 10.1111/j.1365-2230.2008.03007.x
|View full text |Cite
|
Sign up to set email alerts
|

Cefuroxime-induced pemphigus erythematosus in a young boy

Abstract: Pemphigus erythematosus (Senear-Usher syndrome) is a variant of superficial pemphigus with features of both lupus erythematosus and pemphigus. It affects mainly middle-aged adults, and is rarely observed before the age of 20 years. The case of a 14-year-old boy who showed cutaneous lesions suggestive for pemphigus erythematosus is described. Not all laboratory and histopathological investigations confirmed the hypothesis, so a diagnosis of clinical pemphigus erythematosus was made. Systemic steroid therapy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Antibiotics are another group of drugs that could induce bullous diseases. Baroni et al report a case of pemphigus vulgaris possibly associated with the use of amoxicillin and clavulanic acid [14], in another paper and the same authors report cefuroxime as a inducer of the disease [15]. An example of pemphigus caused by biologicals may be found in the paper by Hayashida et al, who indicated that the disease was triggered by secukinumab [16].…”
Section: Omówieniementioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics are another group of drugs that could induce bullous diseases. Baroni et al report a case of pemphigus vulgaris possibly associated with the use of amoxicillin and clavulanic acid [14], in another paper and the same authors report cefuroxime as a inducer of the disease [15]. An example of pemphigus caused by biologicals may be found in the paper by Hayashida et al, who indicated that the disease was triggered by secukinumab [16].…”
Section: Omówieniementioning
confidence: 99%
“…Baroni i wsp. przedstawili przypadek pęcherzycy zwykłej o możliwym związku z przyjmowaniem amoksycyliny z kwasem klawulanowym [14], natomiast w kolejnym opracowaniu ten sam autor wymienił cefuroksym jako induktor choroby [15]. Przykład pęcherzycy wywołanej przez leki biologiczne można odnaleźć w publikacji Hayashida i wsp., którzy jako lek indukujący chorobę wskazali sekukinumab [16].…”
Section: Omówienieunclassified
“…Several mechanisms have been postulated in the pemphigus onset due to non-thiol and non-phenol drugs as overexpression of target antigens on keratinocyte membrane, hyperactivation of the immune system, increase of the local immune response and release of plasminogen activators by keratinocytes (Wolf et al, 1991). Literature data showed increasing evidence of cases of pemphigus due to several systemic drugs penicillamine (Popadic, Skiljevic, & Medenica, 2009), penicillin (Heymann, Chodick, Kramer, Green, & Shalev, 2007), ampicillin (Hodak, Ben-Shetrit, Ingber, & Sandbank, 1990), amoxicillin/clavulanic acid (Baroni, Russo, Faccenda, & Piccolo, 2012), some cephalosporins (Baroni et al, 2009;Pellicano, Iannantuono, & Lomuto, 1993;Scardina, Conti, & Messina, 2004), quinolones (Anadolu, Birol, Bostanci, & Boyvatt, 2002), most nonsteroidal anti-inflammatory drugs (Durdu, Baba, & Seckin, 2011;Kanitakis, Souillet, Faure, & Claudy, 2001;Laing, Sheretz, & Flowers, 1988;Pompeova, 1981), nifedipine (Ameen, Harman, & Black, 2000), (Parfrey, Clement, Vandenburg, & Wright, 1980). Penicillamine was the first drug described to cause pemphigus (Popadic et al, 2009) and have a similar chemical structure to captopril (Parfrey et al, 1980).…”
Section: Other Non-thiol Non-amide Non-phenolic Drugsmentioning
confidence: 99%
“…Recently, it has also been hypothesized the potential role of amides in the pathogenesis of pemphigus (Lo Schiavo, Sangiuliano, Puca, Brunetti, & Ruocco, 2009;Wolf et al, 1991). Literature data showed increasing evidence of cases of pemphigus due to several systemic drugs penicillamine (Popadic, Skiljevic, & Medenica, 2009), penicillin (Heymann, Chodick, Kramer, Green, & Shalev, 2007), ampicillin (Hodak, Ben-Shetrit, Ingber, & Sandbank, 1990), amoxicillin/clavulanic acid (Baroni, Russo, Faccenda, & Piccolo, 2012), some cephalosporins (Baroni et al, 2009;Pellicano, Iannantuono, & Lomuto, 1993;Scardina, Conti, & Messina, 2004), quinolones (Anadolu, Birol, Bostanci, & Boyvatt, 2002), most nonsteroidal anti-inflammatory drugs (Durdu, Baba, & Seckin, 2011;Kanitakis, Souillet, Faure, & Claudy, 2001;Laing, Sheretz, & Flowers, 1988;Pompeova, 1981), nifedipine (Ameen, Harman, & Black, 2000), Literature data showed increasing evidence of cases of pemphigus due to several systemic drugs penicillamine (Popadic, Skiljevic, & Medenica, 2009), penicillin (Heymann, Chodick, Kramer, Green, & Shalev, 2007), ampicillin (Hodak, Ben-Shetrit, Ingber, & Sandbank, 1990), amoxicillin/clavulanic acid (Baroni, Russo, Faccenda, & Piccolo, 2012), some cephalosporins (Baroni et al, 2009;Pellicano, Iannantuono, & Lomuto, 1993;Scardina, Conti, & Messina, 2004), quinolones (Anadolu, Birol, Bostanci, & Boyvatt, 2002), most nonsteroidal anti-inflammatory drugs (Durdu, Baba, & Seckin, 2011;Kanitakis, Souillet, Faure, & Claudy, 2001;Laing, Sheretz, & Flowers, 1988;Pompeova, 1981), nifedipine (Ameen, Harman, & Black, 2000),…”
Section: Introductionmentioning
confidence: 99%
“…The antibodies recognize the pemphigus foliaceus antigen, desmoglein 1; in addition, immunoglobulin G (IgG) and C3 deposition on cell surface of keratinocytes can be revealed in a group of patients. A positive antinuclear antibody (ANA) is detected in 30%–80% of PE patients but only a few patients have been reported to have PE and lupus erythematosus concurrently 2,3. As for pemphigus vulgaris, several exogenous factors are able to induce PE in genetically predisposed individuals, including drug intake, viral infections, exposure to physical agents, and others.…”
Section: Introductionmentioning
confidence: 99%